SENSITIVITAS GENDER DALAM PERSPEKTIF FEMINISME DI MEDIA MASSA - Wa Ode Nurul Yani (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
Television media’s perception toward women and their issues is only seen from the aspect of symbolic violence which is present on news and pictures or films. So, this symbolic violence is shown in the form of labelization or stigmatization and eufimism. Female television audiences who were interviewed as majority’s informants didn’t fully comprehend gender equality and gender justice, gender sensitivity, women’s right, and women’s empowerment. Informants thought patriarchial culture, discrimination, stigmatization and hegemony toward women was considered as fate that should be sincerely undertook based on religious promises so that they can be in Heaven without demanding women’s right.